Effect of oral high frequency ventilation by jet or oscillator on minute ventilation in normal subjects. Issue 10 (October 1985) - George, R J; Winter, R J; Johnson, M A; Slee, I P; Geddes, D M
Abstract : Normal subjects were asked to breathe through an open ended tube while high frequency oscillations were superimposed on tidal breathing via a side arm, either an eight inch (20 cm) loudspeaker or a jet ventilator being used. Both systems were comfortable and well tolerated. Spontaneous minute ventilation fell by 19-46% at frequencies up to 33 Hz without a rise in transcutaneous PCO2. Maximum ventilatory savings occurred at 1.6 Hz with the jet ventilator (p less than 0.01) and at a frequency corresponding to respiratory system resonance with the loudspeaker. This suggests that during oral high frequency ventilation pulmonary gas exchange is improved and leads to more efficient carbon dioxide excretion for a given minute ventilation. This technique provides a practical and simple method of supplementing breathing in conscious subjects, and it may also have application in the management of patients with acute or chronic respiratory failure, where intubation and conventional ventilation might be avoided.